Congenital Absence of Tracheal or Bronchial Rings. (February 2021) - Smith, Matthew M.; Kou, Yann-Fuu; Schweiger, Claudia; Lehenbauer, David G.; de Alarcon, Alessandro; Rutter, Michael J.
Objective: Congenital airway stenosis secondary to absent tracheal or bronchial rings is a rare congenital anomaly that is difficult to manage both clinically and surgically. This typically manifests as severe segmental tracheomalacia, and only isolated cases with short-term follow-up have been previously described. We aim to describe a series of children with absent tracheal or bronchial rings who underwent surgical management and had long-term follow-up. Study Design: Case series with chart review. Setting: Tertiary care pediatric hospital. Methods: Patients with absent tracheal or bronchial rings from 2002 to 2016. Electronic and paper medical records were queried to obtain demographics, age at diagnosis and surgery, pre- and postoperative symptoms, location of absent rings, procedure performed, length of follow-up, and adjunctive procedures performed. Results: Nine subjects were identified who underwent slide tracheoplasty for correction of congenital absent tracheal or bronchial rings. Age at diagnosis ranged from 10 days to 5 years of age (median, 4 weeks). Age at surgery ranged from 3 weeks to 5 years of age (median, 5 weeks). Six out of 9 subjects were extubated on postoperative day 1. Only 1 subject required additional intervention, which included balloon dilation, tracheobronchial stenting, and aortopexy to alleviate the obstruction. Mean follow-up time was 5.89 years. Conclusions: This is the largest series of children with absent tracheal rings who underwent slide tracheoplasty with long-term follow-up presented to date. Slide tracheoplasty is an effective surgical intervention for the treatment of absent tracheal or bronchial rings in infants and young children.